Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1007/s11207-005-1214-3
|View full text |Cite
|
Sign up to set email alerts
|

N–S Asymmetry in the Solar Differential Rotation During 1957–1993

Abstract: The properties of the differential rotation of the Sun are investigated by using Hα filaments as tracers. Annual average angular velocities of 716 quiescent filaments are determined from Hα photoheliograms of the Abastumani Astrophysical Observatory film collection for the years 1957-1993. The existence of north-south (N-S) asymmetry in Hα filaments rotation is confirmed statistically. The connection of asymmetry with the solar activity cycles is established. It is found that the northern hemisphere rotates fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…For example, it has been found that the northern hemisphere rotates faster during even cycles (20 and 22), while the rotation of the southern hemisphere dominates in odd ones (cycles 19 and 21; Gigolashvili et al 2005), a property that has been also interpreted with theoretical arguments ( Itoh et al 2005).…”
Section: North-south Asymmetrymentioning
confidence: 90%
“…For example, it has been found that the northern hemisphere rotates faster during even cycles (20 and 22), while the rotation of the southern hemisphere dominates in odd ones (cycles 19 and 21; Gigolashvili et al 2005), a property that has been also interpreted with theoretical arguments ( Itoh et al 2005).…”
Section: North-south Asymmetrymentioning
confidence: 90%
“…Hansen & Hansen 1975;Duchlev 2001;Gigolashvili et al 2005), and photospheric magnetic fields (e.g. Antonucci et al 1990;Mouradian & Soru-Escaut 1991;Knaack et al 2004Knaack et al , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to see that Hα filaments and the long-lived magnetic features reveal asymmetry in rotation rate for investigated period (1966)(1967)(1968)(1969)(1970)(1971)(1972)(1973)(1974)(1975)(1976)(1977)(1978)(1979)(1980)(1981)(1982)(1983)(1984)(1985). The N-S asymmetry of rotation rates needs further studies and it will be the subject of our future investigations, carried out by improved statistical investigation, than we used for Hα filaments in earlier works (Gigolashvili et al, 2005;.…”
Section: Discussionmentioning
confidence: 99%
“…Besides sunspots, other features of the solar atmosphere used as tracers of solar rotation are e.g., faculae (Newbegin, and Newton, 1931) and Hα filaments (D'Azambuja and D'Azambuja, 1948;Japaridze and Gigolashvili, 1992;Gigolashvili et al, 1995;Gigolashvili et al, 2003Gigolashvili et al, , 2005Gigolashvili et al, , 2007Gigolashvili, Japaridze, and Kukhianidze, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation